POWERS AND REGIONAL SECURITY SYSTEMS: PARAMETERS AND TYPES OF INVOLVEMENT (POST-SOVIET SPACE CASE STUDY) - EYVAZOV, Jannatkhan (CENTRAL ASIA AND THE CAUCASUS, 2013)
It is hardly possible to correctly and fully assess the functioning and development of a regional security system without presenting a complete account of the entire range of ties and relations among the actors involved and the degree of influence of all the powers concerned. Based on a case study of the post-Soviet space, the author studies the involvement of powers in regional security systems; his analysis of the key parameters of this involvement makes it possible for him to identify and describe two types of involvement: full and partial.